Sphingolipids in mitochondria—from function to disease - Jamil, Maryam; Cowart, Lauren Ashley (Frontiers in Cell and Developmental Biology, 2023)
Sphingolipids are not only structural components of cellular membranes but also play vital roles in cell signaling and modulation of cellular processes. Within mitochondria, sphingolipids exert diverse effects on mitochondrial dynamics, energy metabolism, oxidative stress, and cell death pathways. In this review, we summarize literature addressing the crucial role of sphingolipids in mitochondria, highlighting their impact on mitochondrial dynamics, cellular bioenergetics, and important cell processes including apoptosis and mitophagy.